2021
DOI: 10.2147/ijgm.s342107
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic and Predictive Signature for Lung Adenocarcinoma Derived from Combined Hypoxia and Infiltrating Immune Cell-Related Genes in TCGA Patients

Abstract: Background The hypoxia and immune status of the lung adenocarcinoma (LUAD) microenvironment appear to have combined impacts on prognosis. Therefore, deriving a prognostic signature by integrating hypoxia- and immune infiltrating cell-related genes (H&IICRGs) may add value over prognostic indices derived from genes driving either process alone. Methods Differentially expressed H&IICRGs (DE-H&IICRGs) were identified in The Cancer Genome Atlas transcriptomic data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The risk model promoted individualized treatment and provided potential novel targets for immunotherapy of LUAD patients [25]. Similarly, we also built the predictor based on 12 HRGs and the model performed well with much more higher AUC of ROC than other studies [26,27].…”
Section: Discussionmentioning
confidence: 86%
“…The risk model promoted individualized treatment and provided potential novel targets for immunotherapy of LUAD patients [25]. Similarly, we also built the predictor based on 12 HRGs and the model performed well with much more higher AUC of ROC than other studies [26,27].…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the elucidation of immune-related genes with biological significance and assessment of their prognostic value could aid the diagnosis and treatment of patients with LUAD. Previous studies have demonstrated that abnormally expressed genes can be utilized as prognostic LUAD markers (26)(27)(28). However, only a few previous studies have reported the abnormally expressed immune genes and their immune infiltration role (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of hypoxia‐related genes in prognosis prediction of LUAD has received extensive attention in recent years, 48–51 the role of hypoxia in LUAD was not fully elucidated. Several studies have combined hypoxia and immunization to predict the prognosis of patients with LUAD, and the constructed models also have good predictive performances 51,52 . Therefore, it is still necessary to construct more accurate prediction models of LUAD from multi‐omics levels.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Until now, several hypoxia‐related gene features have been built to predict survival rate of certain tumour types, such as ovarian cancer, 42 renal clear cell carcinoma, 43 hepatocellular carcinoma, 44 breast cancer, 45 melanoma 46 and prostate cancer. 47 Although the role of hypoxia‐related genes in prognosis prediction of LUAD has received extensive attention in recent years, 48 , 49 , 50 , 51 the role of hypoxia in LUAD was not fully elucidated. Several studies have combined hypoxia and immunization to predict the prognosis of patients with LUAD, and the constructed models also have good predictive performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation